Cardiovascular Risk Factor Assessment in Shift Workers in Offshore Oil Rigs in Northern Peru - Palacios Ruesta, Roberto C. (2011)
Objective: To determine the frequency of cardiovascular risk factors in offshore oil rig workers and to assess whether such risk may be associated with assigned tasks and work shifts in an oil company in Northern Peru. Materials and methods: We conducted a cross-sectional study, in which we collected data from the annual occupational medical examinations of workers in an oil company in Northern Peru. We reviewed the occupational records of 263 male workers over 40 years old: 27 office workers from daytime shifts, 89 office-field workers from daytime shifst and 147 sea–field workers from night shifts. Subsequently we determined the cardiovascular risk according to Framingham scores for both total cholesterol and LDL cholesterol, and we obtained the frequency of cardiovascular risk factors comparing these figures between the 3 groups. We also compared the mean Framingham risk level in the three groups of workers. We finally obtained the frequency of workers at high, medium, and low cardiovascular risk, and we also determined how many workers had 1, 2, or more than 3 risk factors according to their assigned tasks and shifts. Results: There was no difference in cardiovascular risk factors assessed in the 3 groups of workers. We found a significantly increased Framingham risk score in persons working in night shifts in sea-field and in those doing office work only during daytime shifts (p <0.05), both based on total cholesterol and LDL-cholesterol values, and the highest percentage of workers with high cardiovascular risk (14.1%, 12.5%), depending on total cholesterol (10.6%, 6.3%) and LDL-cholesterol levels in office workers – both for those doing day shifts in the field and those doing night shifts in the sea–field, respectively, compared to those doing office work only during daytime shifts (0%). Conclusions: There is no increase in cardiovascular risk factors in offshore oil rig workers, but there is an increase in Framingham risk levels, and there is also a higher percentage of workers with high cardiovascular risk according to Framingham scores (12.5% and 6.3%).